Analysis and Visualisation of Research Trends in Tera Hertz Meta Material: A General Review - Chouhan, Jasgurpreet Singh (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Terahertz Metamaterials are a type of Metamaterials, capable of interacting at terahertz (THz) frequencies. The bibliometric analysis had been conducted to understand the active authors, organizations, journals, and countries involved in the research domain of “Terahertz Metamaterials”. All published articles related to “Terahertz Metamaterials” from “Scopus”, were analyzed using the VOS viewer to develop analysis tables and visualization maps.This article had set the objective to consolidate the scientific literature regarding the “Terahertz Metamaterials”and also to find out the trends related to the same.The most active journals in this research domain were Optics Express and Nature Nanotechnology. The most active countries were China, Greece, and the United States of America. The leading organizations were the Ministry of Education of China and Tianjin University of China.The most active authorswere Zhang X., Zhang W., and Averitt R.D.